1975
DOI: 10.1111/j.1432-1033.1975.tb04016.x
|View full text |Cite
|
Sign up to set email alerts
|

Dissociation of Small‐Intestinal Sucrase. Isomaltase Complex into Enzymatically Active Subunits

Abstract: 1 . The sucrase . isomaltase complex from rabbit small intestine dissociated into its subunits upon reaction with citraconic anhydride. They can recombine after deacylation under mild acidic conditions.2. When citraconylated, the subunits could be separated and isolated in a catalytically active form. 3. The previously reported procedure for separation of the subunits by alkaline treatment at pH 9.6 is apparently not due to contaminating degradative enzymes (possibly still present at undetectable levels in the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
9
0

Year Published

1975
1975
1982
1982

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 31 publications
(10 citation statements)
references
References 25 publications
1
9
0
Order By: Relevance
“…Semenza et al (3,9,14) showed the properties of sucrase-isomaltase complex as follows: a sucrase-isomaltase complex is retained by Sephadex G-200 owing to a substrate-enzyme like interaction via its isomaltase site. The purified sucrase isomaltase complex had different catalytic sites for sucrase and isomaltase activities and sucrose and isomaltose were hydrolyzed at different sites; however , elec trophoresis or ultracentrifugation did not dissociate the complex into sucrase and isomaltase; as sucrase and isomaltase formed an enzyme-enzyme complex , if the deficiency of either sucrase or isomaltase was found, always both enzymes were deficient; moreover, they showed that sucrase-isomaltase complex was dissociated by citraconylation into sucrase and isomaltase without cleaving the covalent bond .…”
Section: Discussionmentioning
confidence: 99%
“…Semenza et al (3,9,14) showed the properties of sucrase-isomaltase complex as follows: a sucrase-isomaltase complex is retained by Sephadex G-200 owing to a substrate-enzyme like interaction via its isomaltase site. The purified sucrase isomaltase complex had different catalytic sites for sucrase and isomaltase activities and sucrose and isomaltose were hydrolyzed at different sites; however , elec trophoresis or ultracentrifugation did not dissociate the complex into sucrase and isomaltase; as sucrase and isomaltase formed an enzyme-enzyme complex , if the deficiency of either sucrase or isomaltase was found, always both enzymes were deficient; moreover, they showed that sucrase-isomaltase complex was dissociated by citraconylation into sucrase and isomaltase without cleaving the covalent bond .…”
Section: Discussionmentioning
confidence: 99%
“…isomaltase complex can also be separated through a drastic change of the surface charges by citraconylation. After decitraconylation they seem to recombine under appropriate conditions [9].…”
Section: Numerous Proteins Have Been Found To Be Susceptible To Limitmentioning
confidence: 99%
“…The two subunits can be separated by mild alkaline treatment [8] or by reaction with citraconic anhydride [9]. As a result of the alkaline treatment, a pure active isomaltase as well as an aggregate of inactive sucrase and a small amount of slightly active sucrase were isolated and characterized.…”
mentioning
confidence: 99%
“…These enzymes are known to constitute structural proteins of the membrane, their active sites protruding into the lumen from the membrane surface , being associated with polysaccharide chains (ODA and SEKI , 1966;NISHI and TAKESUE, 1978). Since it has been considered that sucrase and isomaltase form a complex in the microvillous membranes (BRAUN et al, 1975;NISHI and TAKESUE , 1978), and lactase and phloridin hydrolase also form a complex (COLOMBO et al, 1973), one possibility may be that these enzyme proteins assemble into intramembranous particles together with some other integral protein subunits to form a transport channel as mentioned before . If this interpretation is acceptable, it is conceivable that immediately after splitting from maltose by action of membrane maltase, for example, glucose could be transported across the membrane into the cytoplasm through the channel joined by the same maltase, thus implying the close coupling of absorption with the terminal digestion of sugar.…”
Section: Microvilli and Absorptionmentioning
confidence: 99%